Intussusception And Obstructive Ileus Et Causa Caecal Tumor In Children - Y. Kusumo Adi Arji Atmanto; Mutmainnah; Ibrahim Abd. Samad (Nusantara Medical Science Journal, 2024)
Introduction and importance: Intussusception/invagination is a condition where the intestine is folded and infiltrates into other parts of the intestine, which can cause obstructive ileus. One of the causes of intussusception in children is a tumor or colorectal malignancy. Treatment should be started as soon as possible concurrently with fluid resuscitation management. Presentation of cases: A 9-month-old female patient complained of flatulence, inability to defecate, and often color vomiting since 4 days ago. The examination result of 3 three-position abdominal photos is a high obstruction ileus. Exploratory laparotomy, loop modification ileostomy, and to-side anastomosis of the ascending colon and ileum were performed. Histopathological examination of the caecum tissue is non-specific inflammation and lymph nodes with sinus histiocytosis. Discussion: 9 months old is a risk factor for intussusception. The patient's condition is acute. Icteric sclerae or jaundice may occur with gastrointestinal lymphoma tumor types. Histopathological examination shows the process of histiocytosis in the lymph nodes and the activation of adaptive immune cells.   Conclusions: Intussusception is the most common cause of obstructive ileus in children. One of the causes of intussusception in children is a tumor that requires operative management.